Wage Insurance, Part-Time Unemployment Insurance and Short-Time Work in the XXI Century - Pierre Cahuc (Institute of Labor Economics (IZA), 2018)
At the start of the XXI century, characterized by the rise of new forms of employment and of skills requirements, many countries need to adapt their labor market institutions to accompany technological changes and globalization. In this context, unemployment insurance is an essential tool to foster and smooth career paths. Its core components comprise unemployment benefits paid to full-time unemployed workers, monitoring, and counseling. But it is clear that they are not sufficient to cover all risks properly. To deal with this issue, part-time unemployment insurance, short-time work and wage insurance have been tried, at different scales, in several countries over the last decades. This paper surveys the evaluations of these schemes and draws lessons from their results for future research and for labor market institutions.
Keywords: H5; J6; 330; part-time unemployment insurance; wage insurance; short-time work